Advances in visual computing : 12th International Symposium, ISVC 2016, Las Vegas, NV, USA, December 12-14, 2016, proceedings /: 12th International Symposium, ISVC 2016, Las Vegas, NV, USA, December 12-14, 2016, proceedings. (2016) - Unknown
No abstract available